Ceramah Mempertahankan Suasana Lingkungan Hijau yang Berkelanjutan Kepada Pegawai Green School - Nyoman Surya Wijaya; Ni Putu Herni Susanti; I Made Budiarsa; I Made Darsana (Jurnal Ragam Pengabdian, 2025)
This Community Service provides a deeper understanding of the Management and the ranks of teaching staff and employees in the Green School environment, under the auspices of the Kulkul Foundation. The problem faced is maintaining the sustainability of the green environment in a climate change situation as well as the use of surrounding natural resources for environmentally friendly energy. Based on the problems faced by the Kulkul Foundation, the Applied Doctoral Program in Tourism Business of the Institute of Tourism and International Business, through the Post-Director provides knowledge to overcome the problems faced. The purpose of this Community Service is to improve the ability and knowledge of all ranks of Green Schools in maintaining and managing the green environment in a sustainable manner.